Get the answers you've been looking for with the help of IDNLearn.com's expert community. Join our knowledgeable community and get detailed, reliable answers to all your questions.
Sagot :
To determine which of the given quadratic equations has the sum of its roots equal to 4, we can use a property of quadratic equations. For a quadratic equation of the form \(ax^2 + bx + c = 0\), the sum of the roots (\( \alpha + \beta \)) is given by \( -\frac{b}{a} \).
Let's analyze each equation one-by-one to find the sum of the roots:
(a) \( 2x^2 - 4x + 8 = 0 \)
For this equation:
- \( a = 2 \)
- \( b = -4 \)
- The sum of the roots is \( \frac{-(-4)}{2} = \frac{4}{2} = 2.0 \)
(b) \( -x^2 + 4x + 4 = 0 \)
For this equation:
- \( a = -1 \)
- \( b = 4 \)
- The sum of the roots is \( \frac{-(4)}{-1} = \frac{-4}{-1} = 4.0 \)
(c) \( -\sqrt{2}x^2 - \frac{4}{\sqrt{2}}x + 1 = 0 \)
For this equation:
- \( a = -\sqrt{2} \)
- \( b = -\frac{4}{\sqrt{2}} \)
- The sum of the roots is \( \frac{-(-\frac{4}{\sqrt{2}})}{-\sqrt{2}} = \frac{\frac{4}{\sqrt{2}}}{-\sqrt{2}} = -2.0 \)
(d) \( 4x^2 - 4x + 4 = 0 \)
For this equation:
- \( a = 4 \)
- \( b = -4 \)
- The sum of the roots is \( \frac{-(-4)}{4} = \frac{4}{4} = 1.0 \)
After calculating the sum of the roots for each equation, we see that the quadratic equation in option (b), which is \( -x^2 + 4x + 4 = 0 \), has a sum of its roots equal to 4. Therefore, the correct answer is:
(b) [tex]\( -x^2 + 4x + 4 = 0 \)[/tex]
Let's analyze each equation one-by-one to find the sum of the roots:
(a) \( 2x^2 - 4x + 8 = 0 \)
For this equation:
- \( a = 2 \)
- \( b = -4 \)
- The sum of the roots is \( \frac{-(-4)}{2} = \frac{4}{2} = 2.0 \)
(b) \( -x^2 + 4x + 4 = 0 \)
For this equation:
- \( a = -1 \)
- \( b = 4 \)
- The sum of the roots is \( \frac{-(4)}{-1} = \frac{-4}{-1} = 4.0 \)
(c) \( -\sqrt{2}x^2 - \frac{4}{\sqrt{2}}x + 1 = 0 \)
For this equation:
- \( a = -\sqrt{2} \)
- \( b = -\frac{4}{\sqrt{2}} \)
- The sum of the roots is \( \frac{-(-\frac{4}{\sqrt{2}})}{-\sqrt{2}} = \frac{\frac{4}{\sqrt{2}}}{-\sqrt{2}} = -2.0 \)
(d) \( 4x^2 - 4x + 4 = 0 \)
For this equation:
- \( a = 4 \)
- \( b = -4 \)
- The sum of the roots is \( \frac{-(-4)}{4} = \frac{4}{4} = 1.0 \)
After calculating the sum of the roots for each equation, we see that the quadratic equation in option (b), which is \( -x^2 + 4x + 4 = 0 \), has a sum of its roots equal to 4. Therefore, the correct answer is:
(b) [tex]\( -x^2 + 4x + 4 = 0 \)[/tex]
Thank you for contributing to our discussion. Don't forget to check back for new answers. Keep asking, answering, and sharing useful information. IDNLearn.com has the answers you need. Thank you for visiting, and we look forward to helping you again soon.